Ball milling: a simple and efficient method for quantitative solvent-free synthesis of new potential bioactive Ni(II) and Co(II) complexes. Issue 1 (1st January 2021) - Zaky, Rania; Al-Dawood, Aisha Y.; Al-Ahmed, Zehba A.
ABSTRCT: A simple and efficient technique for quantitative solvent-free synthesis of Ni (II) and Co (II) complexes by using ball milling as a green strategy is studied. The isolated solid compounds will be characterized using micro-analytical, thermo-gravimetric, magnetic and spectroscopic studies. Theoretical studies were carried out by applying DFT theory to predict the optimized configuration for all isolated solid complexes. Moreover, the in vitro antimicrobial activity assay versus fungi and bacteria via MIC technique has higher potency of Ni (II) than Co (II). The in vitro cytotoxicity of human muscle rhabdomyosarcoma (RD) via MTT technique and the antioxidant by DPPH free radical scavenging has higher inhibitory effect on complexes than free ligand. The cyclic voltammetry of Co(II) in absence/presence of H2 BHNH was investigated to realize the significant effect of complex formation on the electrochemical manners of Co(II).